Leveraging the Sample Throughput of NGS with the Fulcrum of Bar-coded Sequence Capture Technology - Leonard, J.T. (Association of Biomolecular Resource Facilities, 2010)
RP-28 Massively parallel DNA sequencing, when combined with sequence capture methodologies, reduces the time, cost, and effort required to interrogate multiple genomic loci. We have demonstrated that high levels of multiplexing are achievable by combining HybSelect parallel sample processing capabilities with bar-coding reagents. After automated sequence capture with ™, targeted next-generation sequencing (tNGS) was carried out on the ™ Sequencing System. The use of barcodes on the sequencing adaptors allows the confident identification and tracking of samples, and greatly strengthens traditional LIMS (Laboratory Information Management Systems) in regulated production sequencing environments. Bar-coded targets from hundreds of individuals can be sequenced per week by integrating the workflows of the SOLiD System with a febit HybSelect instrument. We have applied this process to several human disease related targets and will present results from first studies.